Frekuensi MPTS Pangan dari Hutan Rakyat di Desa Paku Kecamatan Binuang Kabupaten Polewali Mandar - Mushawwir, Aan; Irundu, Daud; Carong, Suparjo Razasli; Indhasari, Fitri (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2021)
The need for food fulfillment at the national level is currently the government's concern, community forests have a role in contributing to efforts to increase food potential, the implementation of MPTS is a good strategy for food oriented community forest management. Paku Village, Binuang District, Polewali Mandar Regency is one of the areas that has an area of 1000 Ha, which also produces MPTS. The aim of this research was to determine the frequency of MPTS in the community forest of Paku Village. The method used in this research was the descriptive quantitative analysis. The results showed that the percentage of MPTS and forest wood in the community forest of Paku Village was 63,32% and 36,68%. The highest percentage of MPTS presence in Paku Village is cocoa as much as 41,46% and the lowest is coconut, sugar palm, guava, oranges, kedondong as much as 0,61%, MPTS frequency from 12 plots obtained the percentage of presence of one hightest frequency is 80,4% with the attendance value of one to five MPTS.